Pemanfaatan Sistem Informasi Akuntansi dalam Menunjang Pengendalian Internal Pemberian Kredit pada Bank Negara Indonesia - Stefhany Angela Davit; Devi Astriani; Ihsan Nasihin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to assess and understand how information systems are used to support internal control during the Bank Negara Indonesia (BNI) credit granting process. Accounting information systems (AIS) play an important role in ensuring the accuracy and reliability of financial data, thereby reducing the potential for errors and fraud. .The research method uses qualitative methods. Data collection was carried out through intensive interviews with management and related employees as well as examining internal documents. The analysis techniques used were data collection, data presentation, data reduction and drawing conclusions. The results show that the implementation of SIA at BNI has significantly increased the efficiency of internal control and the lending process while minimizing related risks. This improvement, despite several cases of non-performing loans (NPL), is in line with Mulyadi's internal control principles, which focus on a clear organizational structure , effective authority systems, and good operational practices.